Allegorie des verdrängten Mitläufertums: Carl Merz’ und Helmut Qualtingers Herr Karl als österreichische ‚Banalität des Bösen‘ - Milkovits, Daniel (DIVE-IN – An International Journal on Diversity and Inclusion, 2023)
With Der Herr Karl (1961), Carl Merz and Helmut Qualtinger created a folk play of a ‘critical, myth-destroying form’ (Bobinac 1992) which is unique in Austrian theatre history. The scandal which this one-hour monodrama caused when it was first broadcast on Austrian television was also due to the unmasking character drawing: In the behaviour of the titular fellow traveller and opportunist ‘Herr Karl’, the audience recognised itself – the post-war mentality of repressing, forgetting and relativising found itself shaken to its foundations. The article aims to examine to what extent Hannah Arendt’s reflections on the ‘Banality of Evil’ are actually applicable to Merz and Qualtinger’s play and which aspects of Austrian mentality history become visible in it. In particular, the Austrian remembrance culture and its way of dealing with the traumatic happenings could become evident – especially in a nation that tried to posit itself as the first ‘victim’ of Hitler’s Germany even before the end of the war